2008
DOI: 10.30638/eemj.2008.082
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Cellulose as Support Material for the Immobilization of Denitrifying Bacteria

Abstract: The purpose of this study was to investigate the immobilization of denitrifying bacteria on microbial cellulose (MC) for biological denitrification. A novel denitrifying bacterium, Pseudomonas stutzeri, was immobilized in microbial cellulose and introduced into an up flow packed bed reactor in order to remove nitrate from synthetic influent. The MC presented the high biomass concentration throughout the experiment, achieving 3.4 mg biomass/g support. The efficiency of the system for denitrification was tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…The higher kinetics constant for the immobilized systems demonstrated that the entrapment in hydrogel matrices increased the degradation ability of this microorganism. These results were in agreement with those reported by Rezaee et al They determine that the immobilization of P. stutzeri in Ca‐alginate increased the stability of a microbial system for denitrification of effluents, allowing its application under extreme environmental conditions.…”
Section: Resultssupporting
confidence: 93%
“…The higher kinetics constant for the immobilized systems demonstrated that the entrapment in hydrogel matrices increased the degradation ability of this microorganism. These results were in agreement with those reported by Rezaee et al They determine that the immobilization of P. stutzeri in Ca‐alginate increased the stability of a microbial system for denitrification of effluents, allowing its application under extreme environmental conditions.…”
Section: Resultssupporting
confidence: 93%
“…3c), an uneven surface was seen, which indicated that the surface of the individual fibers had been changed drastically. Such kind of rupture of cell wall surface or a visible increase of porosity was believed to increase the specific surface area of the carriers, which contributed to the absorption of cells (Rezaee et al 2008). During the hydrolysis, it was observed that the porous corn stalk cells which could embed the yeast cells were disrupted greatly after 6 h (Fig.…”
Section: Cell-holding Specificity Of Corn Stalkmentioning
confidence: 97%
“…The cellulose is highly crystalline, has high water absorption capacity and mechanical strength in the wet state, ultra fine network structure (Astley, Chanliaud, & Donald, 2001). Taking advantage of these properties researchers have tried to immobilize various bacteria on microbial cellulose (Rezaee, Godini, & Bakhtou, 2008) and tried to use it to carry out alcoholic fermentations (Iconomopoulou, Kanellaki, Psarianos, & Koutinas, 2000) and industrial waste water treatments (Rezaee, Godini, Naimi, & Masombaigi, 2008).…”
Section: Introductionmentioning
confidence: 99%